Potentiation of IL-4 Signaling by Retinoic Acid in Intestinal Epithelial Cells and Macrophages—Mechanisms and Targets - Chen, Celine; Smith, Allen D.; Cheung, Lumei; Pham, Quynhchi; Urban, Joseph F.; Dawson, Harry D. (Frontiers in Immunology, 2020)
We previously demonstrated that IL4, IL13, CLCA1 and CCL26 mRNA were significantly upregulated in the lungs of pigs given a low dose of all trans-retinoic acid (ATRA) and infected with Ascaris suum. We also demonstrated that in vitro ATRA induced a state of partial alternative activation in porcine macrophages (Mφs) and amplified certain aspects of M2a activation induced by IL-4. Given these results, we tested the effect of ATRA on IL-4 responses in two porcine intestinal epithelial cell lines, IPEC1 and IPEC-J2 and observed that ATRA increased mRNA for the IL-4 receptor alpha chain. ATRA also increased IL-4 induced phosphorylation of signal transducer and activator of transcription 6 (STAT6) and mRNA expression of the chloride channel, calcium activated, family member 1 (CLCA1), important for mucus formation, and chemokine (C-C motif) ligand 26 (CCL26), a potent eosinophil chemoattractant. We extended these findings to human Mφ THP-1 cells and showed that ATRA synergistically increased IL-4–induced CCL2, CCL13 and CCL26 mRNA and protein levels. Transglutaminase 2 mRNA, protein, and enzyme activity were synergistically induced in THP-1 cells pretreated with ATRA and then treated with IL-4, thus, ATRA increased signaling in response to IL-4 in porcine epithelial cells and porcine and human macrophages. Given the prevalence of allergic and parasitic diseases worldwide and the close similarities in the porcine and human immune responses, these findings have important implications for the nutritional regulation of allergic inflammation at mucosal surfaces.